Students’ Alternative Conceptions about Electricity and Effect of Inquiry-Based Teaching Strategies - Osta, Iman (2009)
This study attempted to investigate the alternative conceptions that a group of 12 Lebanese students in a grade 9 class hold about electricity. It also attempted to evaluate learning outcomes of implementing in that class an inquiry-based module for the acquisition of conceptual understanding of basic concepts in electricity. Fourteen mostly subjective tests were administered throughout the implementation phase of the inquiry-based module to assess the evolution of participants’ conceptions. The instrument DIRECT (Version 1.0) focusing on conceptual understanding was used as a post-instructional test to measure acquisition of understanding. The findings revealed that most of the alternative conceptions reported in literature were found amongst the participants. Results of the post-testing showed that the implemented inquiry-based approach was successful in enhancing participants’ conceptual understanding of the targeted DC circuit concepts.